Case report: Renal cell carcinoma with metastasis to the myometrium. Issue 6 (June 2014) - Rahbar, Haider M.; Kumar, Ramesh K.; Dalela, Deepansh; Hanna, Rabbie; Gupta, Nilesh; Rogers, Craig G.
Abstract Renal cell carcinoma (RCC) is well known for its ability to metastasize to different organs, but the involvement of gynecological organs is rare. Our case represents the first case of bilateral RCC with metastasis to the myometrium. The patient was a 60‐year‐old woman who underwent bilateral robotic partial nephrectomy surgeries for clear cell RCC, low‐grade, low‐stage with negative margins. Her 1‐year postoperative computed tomography scan showed an enlarging necrotic uterine mass. She underwent a debulking excision, including hysterectomy, with pathology showing metastatic RCC to the uterus. The patient developed widespread metastatic disease, and died months later of metastatic RCC.